Acquired pellicle engineering with proteins/peptides: Mechanism of action on native human enamel surface. (April 2021) - Pelá, Vinícius Taioqui; Buzalaf, Marília Afonso Rabelo; Niemeyer, Samira Helena; Baumann, Tommy; Henrique-Silva, Flávio; Toyama, Danyelle; Crusca, Edson; Marchetto, Reinaldo; Lussi, Adrian; Carvalho, Thiago Saads
Graphical abstract: Highlights: CaneCPI-5, statherin and hemoglobin protect native enamel against dental erosion. The combination group provides the best protection against dental erosion. Mechanism of action of how the proteins/peptides act on the salivary pellicle. Acquired pellicle engineering protects enamel demineralization. Abstract: Objective: This study investigated the mechanism of action of different proteins/peptides (separately or in combination), focusing on how they act directly on the native enamel surface and on modifying the salivary pellicle. Methods: A total of 170 native human enamel specimens were prepared and submitted to different treatments (2 h; 37 °C): with deionized water, CaneCPI-5, Hemoglobin, Statherin, or a combination of all three proteins/peptides. The groups were subdivided into treatment acting on the enamel surface (NoP – absence of salivary pellicle), and treatment modifying the salivary pellicle (P). Treatment was made (2 h; 37 °C) in all specimens, and later, for P, the specimens were incubated in human saliva (2 h; 37 °C). In both cases, the specimens were immersed in 1% citric acid (pH 3.6; 2 min; 25 °C). Calcium released from enamel (CaR) and its relative surface reflection intensity (%SRI) was measured after 5 cycles. Between-group differences were verified with two-way ANOVA, with "presence of pellicle" and "treatment" as factors (α = 0.05). Results: The presence of pellicle provided better protection regarding %SRI (p < 0.01), but not regarding CaR (p = 0.201). In relation to treatment, when compared to the control group, all proteins/peptides provided significantly better protection (p < 0.01 for %SRI and Car). The combination of all three proteins/peptides demonstrated the best protective effect (p < 0.01 for %SRI). Conclusion: Depending on the protein or peptide, its erosion-inhibiting effect derives from their interaction with the enamel surface or from modifying the pellicle, so a combination of proteins and peptides provides the best protection. Clinical significance: The present study opens a new direction for a possible treatment with a combination of proteins for native human enamel, which can act directly on the enamel surface as well on the modification of the salivary pellicle, for the prevention of dental erosion.